Productivity change and its drivers for the Chilean water companies: A comparison of full private and concessionary companies. (10th May 2018) - Molinos-Senante, María; Porcher, Simon; Maziotis, Alexandros
Abstract: The privatization of the water industry has aroused interest in comparing the performance of public vs. private water companies. However, little research has been conducted to compare the performances of full private (FPWCs) and concessionary water companies (CWCs). This study estimates and compares the productivity growth and its drivers (efficiency, technical and scale change) for a sample of Chilean FPWCs and CWCs over the 2007–2015 period using the input distance function. Both types of water companies showed deteriorations in productivity growth, with CWCs exhibiting higher rates of negative productivity growth than FPWCs. For FPWCs, any gains in efficiency and scale were outstripped by negative technical change. CWCs did not improve their performance in any of the three components of productivity change. The comparison of productivity change between FPWCs and CWCs is essential to support decision-making therefore, this study is of great interest for policymakers worldwide who are developing policies aimed at privatizing water companies. Highlights: The productivity change of full private and concessionary water companies was compared. Stochastic frontier techniques were used to compute productivity and its drivers. Non-revenue water contributed significantly to the productivity regression. Improve drinking water and wastewater treatment quality led to higher input requirements.